Outcomes after non-operative management of perforated diverticular disease: a population-based cohort study. Issue 2 (22nd April 2021) - Adiamah, A; Ban, L; Otete, H; Crooks, C J; West, J; Humes, D J
Abstract: Background: The management of perforated diverticular disease has changed in the past 10 years with a move towards less surgical intervention. This population-based cohort study aimed to define the risk of death and readmission following non-operative management of perforated diverticular disease. Methods: Patients diagnosed with perforated diverticular disease and managed without surgery were identified from the linked Clinical Practice Research Datalink and Hospital Episode Statistics data from 2000 to 2013. The outcomes were 1-year case fatality, readmissions, and surgery at readmission. Results: In total, 880 patients with perforated diverticular disease were managed without surgery, comprising 523 women (59.4 per cent). The 1-year case fatality rate was 33.2 per cent (293 of 880). The majority of deaths occurred in the first 90 days after the index admission, with a 90-day case fatality rate of 28.8 per cent. The 90-day survival rate varied by age, and was 97.2 per cent among those aged less than 65 years, compared with 85.0 per cent for those aged between 65 and 74 years, and 47.7 per cent in those at least 75 years old. Of 767 patients discharged from hospital, 250 (32.6 per cent) were readmitted (47 elective, 6.1 per cent; 203 emergency, 26.5 per cent) during a median of 1.6 (i.q.r. 0.1–3.9) years of follow-up, with similar proportions in each age category. In the first year of follow-up, only 5.1 per cent of patients required surgery, of whom 16 of 767 (2.1 per cent) required elective and 23 (3.0 per cent) emergency operation. Conclusion: Non-operative management of perforated diverticulitis in those aged less than 65 years is feasible and safe. Reintervention rates following conservative management were low across all age categories. Abstract : Among patients treated conservatively for perforated diverticulitis, 32.6 per cent of those discharged from hospital required emergency readmission during follow-up. Of these, only 3.0 per cent required emergency surgery. Reintervention rates after conservative management of perforated diverticular disease are reassuringly low.